Usefullness of Dynamic CT for Acute Cholangitis - Gabata, Toshifumi (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2012)
In the first edition of the guidelines on acute cholangitis and cholecystitis (2005), acute cholangitis was not diagnosed by imaging diagnosis such as CT, US, and MRI. However, contrast enhanced dynamic CT can show characteristic imaging findings of acute cholangitis. In cases of acute cholangitis, inhomogeneous hepatic parenchymal enhancement (nodular, patchy, wedge-shaped, or geographic) is seen on the arterial phase of dynamic CT. This enhancement disappears on the portal and the equilibrium phases. The etiology of inhomogeneous enhancement is a decrease in the peripheral portal venous flow and a compensatory increase of hepatic arterial flow by peribiliary inflammation of the portal tract (Glisson's sheath). In conclusion, when clinically acute cholangitis is suspected, contrast enhanced dynamic CT is recommended for prompt diagnosis and treatment of cholangitis.